Family building and pregnancy experiences of cisgender sexual minority womenAJOG Global Reports at a Glance - Diana M. Tordoff, PhD, MPH; Heidi Moseson, PhD, MPH; Sachiko Ragosta; Jen Hastings, MD; Annesa Flentje, PhD; Matthew R. Capriotti, PhD; Micah E. Lubensky, PhD; Mitchell R. Lunn, MD, MAS; Juno Obedin-Maliver, MD, MPH, MAS (Elsevier, 2024)
BACKGROUND: Although 10% to 20% of cisgender women aged 18 to 40 years have a sexual minority identity (eg, bisexual, lesbian, and queer), there is limited research on the family building and pregnancy experiences of sexual minority cisgender women. Improving our understanding of the family building and pregnancy experiences of cisgender sexual minority women is critical for improving the perinatal health of this population. OBJECTIVE: This study aimed to compare the mode of family building, past pregnancy experiences, and future pregnancy intentions among cisgender sexual minority women by sexual orientation. STUDY DESIGN: This is an observational study which was conducted using cross-sectional data collected in 2019 from a national sample of 1369 cisgender sexual minority women aged 18 to 45 years. RESULTS: Most participants (n=794, 58%) endorsed multiple sexual orientations, most commonly queer (n=641, 47%), lesbian (n=640, 47%), and/or bisexual (n=583, 43%). There were 243 (18%) cisgender sexual minority women who were parents. Pregnancy was used by 74% (181/243) of women to build their families. Among participants who used pregnancy, 60% (108/181) became pregnant through sexual activity with another parent of the child, whereas 27% (64/243) of women used donor sperm. An additional 10% (n=24) became parents through second-parent adoption, 10% (n=25) through adoption, and 14% (n=35) through step-parenting. Bisexual women more often used sexual activity to become parents (61/100, 61%) compared with queer (40/89, 45%) and lesbian women (40/130, 31%). In contrast, lesbian (50/130, 39%) and queer (25/89, 27%) women more often used donor sperm to become parents compared with bisexual women (11/100, 11%). Among the 266 (19%) cisgender sexual minority women who had ever been pregnant, there were 545 pregnancies (mean, 2.05 pregnancies per woman). Among those pregnancies, 59% (n=327) resulted in live birth, 23% (n=126) resulted in miscarriage, 15% (n=83) resulted in abortion, and 2% (n=9) resulted in ectopic pregnancy. A quarter of women had future pregnancy intentions, with no differences by sexual orientation. Overall, few participants (16%) reported that all of their healthcare providers were aware of their sexual orientation. CONCLUSION: Cisgender sexual minority women primarily built their families through pregnancy and a quarter have future pregnancy desires. In addition, there were important differences in family building methods used by sexual orientation. Providers should be aware of the pregnancy and family-building patterns, plans, and needs of cisgender sexual minority women.